Comprehensive genotype–phenotype correlations between NLRP7 mutations and the balance between embryonic tissue differentiation and trophoblastic proliferation. Issue 9 (5th August 2014) - Nguyen, Ngoc Minh Phuong; Zhang, Li; Reddy, Ramesh; Déry, Christine; Arseneau, Jocelyne; Cheung, Annie; Surti, Urvashi; Hoffner, Lori; Seoud, Muhieddine; Zaatari, Ghazi; Bagga, Rashmi; Srinivasan, Radhika; et al.
Abstract : Background: Hydatidiform mole (HM) is a human pregnancy with excessive trophoblastic proliferation and abnormal embryonic development that may be sporadic or recurrent. In the sporadic form, the HM phenotype is driven by an abnormal ratio of paternal to maternal genomes, whereas in the recurrent form, the HM phenotype is caused by maternal-recessive mutations, mostly in NLRP7, despite the diploid biparental origin of the HM tissues. In this study, we characterised the expression of the imprinted, maternally expressed gene, CDKN1C (p57 KIP2 ), the genotype, and the histopathology of 36 products of conception (POC) from patients with two defective alleles in NLRP7 and looked for potential correlations between the nature of the mutations in the patients and the various HM features. Methods/results: We found that all the 36 POCs are diploid biparental and have the same parental contribution to their genomes. However, some of them expressed variable levels of p57 KIP2 and this expression was strongly associated with the presence of embryonic tissues of inner cell mass origin and mild trophoblastic proliferation, which are features of triploid partial HMs, and were associated with missense mutations. Negative p57 KIP2 expression was associated with the absence of embryonic tissues and excessive trophoblastic proliferation, which are features of androgenetic complete HMs and were associated with protein-truncating mutations. Conclusions: Our data suggest that NLRP7, depending on the severity of its mutations, regulates the imprinted expression of p57 KIP2 and consequently the balance between tissue differentiation and proliferation during early human development. This role is novel and could not have been revealed by any other approach on somatic cells.